2019
DOI: 10.1111/cas.14174
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17 is associated with expression of programmed cell death 1 ligand 1 in ovarian carcinoma

Abstract: The programmed cell death 1/programmed cell death 1 ligand 1 pathway was successfully targeted in cancer immunotherapy. Elevated interleukin‐17 (IL‐17), which is known in autoimmune diseases, has recently been recognized in cancer patients. We investigated the role of IL‐17 in the regulation of expression of programmed cell death 1 ligand 1 in ovarian cancer by evaluating changes in the number of IL‐17‐producing cluster of differentiation 4 helper T cells (Th17) and γδT cells (γδT17) in PBMC of 52 gynecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Neutrophils can modulate and suppress the activity of T cells in the OvCA microenvironment [80,81] and can facilitate the immune escape of OvCA cells by upregulating the expression of PD-L1 [80] (Figure 1). Another recent study confirmed that NLR ratio positively correlates with increased Th17/IL-17 levels and expression of PD-L1 in ovarian carcinoma [82].…”
Section: Neutrophilsmentioning
confidence: 69%
“…Neutrophils can modulate and suppress the activity of T cells in the OvCA microenvironment [80,81] and can facilitate the immune escape of OvCA cells by upregulating the expression of PD-L1 [80] (Figure 1). Another recent study confirmed that NLR ratio positively correlates with increased Th17/IL-17 levels and expression of PD-L1 in ovarian carcinoma [82].…”
Section: Neutrophilsmentioning
confidence: 69%
“…In addition, the association between IL-17 and PD-1/PD-L1 has been observed in several kinds of carcinoma. Aotsuka et al (36) demonstrated that IL-17A induced the expression of PD-L1 in ovarian cancer cell lines. Wang et al (37) observed that IL-17A upregulated PD-L1 protein levels in human prostate cancer and human colon cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have abilities to recognize different tumor cells in a major histocompatibility complex (MHC)-unrestricted manner and lyse cancer cells by producing chemokines and cytokines, or by direct contact with cancer cells through the death receptor signal (19,20), which suggests that γδ T cells may have a potential role in antitumor immunotherapy. However, accumulating evidence suggests that γδ T cells also play a protumor role mainly by expressing interleukin-17 (IL-17) in several cancers (17,(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%